Zahirah al-`adl Fi Al-Nikah - Budiono, Budiono (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2018)
Marriage is one of the topics that get the most attention. Choosing a husband is the main right of a woman without intervention from anyone, especially the marriage guardian or her father. the phenomenon of the end of this age, there are so many marriage guardians that make their daughters' marriages hampered or complicate them with illogical excuses. Most parents see from the point of view of wealth, thus prohibiting the marriage of their daughters because they do not want their children after marriage to experience misery in life. The need for marriage is basic that cannot be represented. In a hadith it is said, that a daughter has full rights to determine her future husband, or if the child does not agree with her guardian's choice then it cannot be forced. Prohibiting the marriage of women on the side of the guardian is an act of wrongdoing and will occur slander (disaster) and extensive damage on earth. The scholars agree, that the guardian has no right to prevent the women he escorts from marrying, even though the applicant is as kufu 'and with the dowry of mitsl. If the guardian hinders the marriage, the bride has the right to report her case to the court so that the marriage can take place. Under these circumstances, the trusteeship does not move from the wrong guardian to another guardian, but is directly handled by the judge himself, because blocking it is an act of wrongdoing. [Perkawinan merupakan salah topik yang mendapatkan perhatian yang sangat besar. Memilih suami adalah hak utama seorang wanita tanpa intervensi dari siapapun khususnya wali nikah atau ayahnya. fenomena akhir zaman ini, ada begitu banyak wali nikah yang membuat pernikahan anak perempuannya terhambat atau mempersulitnya dengan dalih yang tak logis. Kebanyakan orang tua melihat dari sudut pandang harta kekayaan, sehingga melarang perkawinan putrinya dikarenakan tidak ingin anaknya pasca perkawinan mengalami kesengsaraan dalam hidup. Kebutuhan akan nikah itu asasi yang tidak bisa diwakili. Dalam sebuah hadis dikatakan, bahwa anak perempuan memiliki hak penuh untuk menentukan calon suaminya, atau jika si anak tidak setuju atas pilihan walinya maka tidak boleh dipaksakan. Melarang perkawinan perempuan dari pihak wali merupakan perbuatan zalim dan akan terjadi fitnah (bencana) dan kerusakan yang luas di muka bumi. Para ulama sependapat, bahwa wali tidak berhak menghalangi perempuan yang diwalikannya supaya tidak kawin, padahal si pelamar itu se-kufu’ dan dengan mahar mitsl. Jika wali menghalangi pernikahan tersebut, calon pengantin wanita berhak mengadukan perkaranya kepada pengadilan agar perkawinan tersebut dapat dilangsungkan. Dalam keadaan seperti ini, perwalian tidak pindah dari wali yang zalim kepada wali yang lainnya, tetapi langsung ditangani oleh hakim sendiri, sebab menghalangi hal tersebut adalah suatu perbuatan yang zalim.]